2011
DOI: 10.1073/pnas.1019432108
|View full text |Cite
|
Sign up to set email alerts
|

Antarctic and Arctic populations of the ciliate Euplotes nobilii show common pheromone-mediated cell-cell signaling and cross-mating

Abstract: Wild-type strains of the protozoan ciliate Euplotes collected from different locations on the coasts of Antarctica, Tierra del Fuego and the Arctic were taxonomically identified as the morpho-species Euplotes nobilii, based on morphometric and phylogenetic analyses. Subsequent studies of their sexual interactions revealed that mating combinations of Antarctic and Arctic strains form stable pairs of conjugant cells. These conjugant pairs were isolated and shown to complete mutual gene exchange and cross-fertili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 42 publications
(37 reference statements)
1
38
0
Order By: Relevance
“…A synergistic force is arguably represented also by the capacity of these populations to communicate and interact, like other Euplotes populations, via diffusible signaling pheromones that each cell synthesizes to promote not only mating but also vegetative growth (Luporini et al 2005). Because of their structural homology, these pheromones are mutually crossreactive and their structural specificities are such to secure unmatched long-lasting activity and wide-range dispersal in any marine environment (Di Giuseppe et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A synergistic force is arguably represented also by the capacity of these populations to communicate and interact, like other Euplotes populations, via diffusible signaling pheromones that each cell synthesizes to promote not only mating but also vegetative growth (Luporini et al 2005). Because of their structural homology, these pheromones are mutually crossreactive and their structural specificities are such to secure unmatched long-lasting activity and wide-range dispersal in any marine environment (Di Giuseppe et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…With the extension of the study of mating interactions to Fuegian and Arctic strains it was first shown that some pheromones structurally characterized from Antarctic and Arctic strains were represented by helical proteins in all members of the same homologous family (Alimenti et al 2009;Di Giuseppe et al 2011). Subsequently, it was observed that some Antarctic strains were fully able to form stable mating pairs not only in mixtures with Fuegian strains (with which there was sharing of identical SSU-rRNA nuclear gene sequences), but also in mixtures with Arctic strains (from which there were sequence divergences), thus implying a genetic continuity among the Antarctic, Fuegian and Arctic E. nobilii populations represented by these strains.…”
Section: Mating and Breeding Interactionsmentioning
confidence: 99%
“…The scale bar corresponds to two substitutions per 100 nucleotide positions. The accession numbers of the sequences used to generate the tree are indicated for each species with the exception of E. nobilii, E. petzi, and E. euryhalinus, for which the accession numbers of the multiple sequences that have been used are reported in Di Giuseppe et al (2011Giuseppe et al ( , 2014 and Table 2 (this article), respectively. In accord with Jiang et al (2010a, b) and Chen et al (2013), Certesia quadrinucleata and Aspidisca steini (species of a sister clade of Euplotes) were used as outgroups Hydrobiologia nucleotide substitution was identified within either of the two sets of strains, while four substitutions were detected between the two sets of strains, determining their consequent separation into two distinct clusters (Fig.…”
Section: Genetic Relationshipsmentioning
confidence: 99%
“…This collection was for a long time essentially used to investigate molecular mechanisms underlying cold adaptation (Pedrini et al, 2007;Alimenti et al, 2009;Vallesi et al, 2010Vallesi et al, , 2012Chiappori et al, 2012;Candelori et al, 2013;Geralt et al, 2013). Only more recently has it turned out to be of research interest also within a biogeographic and ecological perspective, in relation to morphological and genetic evidence that co-specificity exists among strains inhabiting opposite sides of the globe (Di Giuseppe et al, 2011, 2013a.…”
Section: Introductionmentioning
confidence: 98%
“…The NMR solution structures are known only for four of them, which could be purified in larger amounts, namely En-1, En-2, En-6 and En-A1 Placzek et al 2007;Di Giuseppe et al 2011) ( Figure 4B).…”
Section: Euplotes Nobilii Pheromonesmentioning
confidence: 99%